The mechanisms and treatment of asphyxial encephalopathy - Wassink, Guido; Gunn, Eleanor R.; Drury, Paul P.; Bennet, Laura; Gunn, Alistair J. (Frontiers in Neuroscience, 2014)
Acute post-asphyxial encephalopathy occurring around the time of birth remains a major cause of death and disability. The recent seminal insight that allows active neuroprotective treatment is that even after profound asphyxia (the “primary” phase), many brain cells show initial recovery from the insult during a short “latent” phase, typically lasting approximately 6 h, only to die hours to days later after a “secondary” deterioration characterized by seizures, cytotoxic edema, and progressive failure of cerebral oxidative metabolism. Although many of these secondary processes are potentially injurious, they appear to be primarily epiphenomena of the “execution” phase of cell death. Animal and human studies designed around this conceptual framework have shown that moderate cerebral hypothermia initiated as early as possible but before the onset of secondary deterioration, and continued for a sufficient duration to allow the secondary deterioration to resolve, has been associated with potent, long-lasting neuroprotection. Recent clinical trials show that while therapeutic hypothermia significantly reduces morbidity and mortality, many babies still die or survive with disabilities. The challenge for the future is to find ways of improving the effectiveness of treatment. In this review, we will dissect the known mechanisms of hypoxic-ischemic brain injury in relation to the known effects of hypothermic neuroprotection.